A benzothiazole-based fluorescent probe for selective detection of H2S in living cells and mouse hippocampal tissues. (March 2017) - Liu, Yi; Ding, Yan; Huang, Jie; Zhang, Xiaofei; Fang, Tongyong; Zhang, Yuyun; Zheng, Xian; Yang, Xia
Abstract: This study reports a benzothiazole-based fluorescent probe EPS-HS for real-time detection of H2 S. The probe is characterized in a large red-shift, good selectivity, high sensitivity and favorable biocompatibility. We measured the detection limit of EPS-HS in PBS buffer and fetal bovine serum. Moreover, in HT22 living cell imaging studies, EPS-HS showed good cell permeability and H2 S could be detected within the cells. Furthermore, in situ visualization of H2 S was performed on the hippocampal slices of normal mice with EPS-HS. We were also able to estimate the concentration of sulfide in mouse hippocampus tissues. The probe will be applied for better treatment of neurological deficits caused by damage to the hippocampus. Highlights: We designed and synthesized a benzothiazole-based fluorescent probe EPS-HS for selective detection of H2 S. The probe EPS-HS showed good cell permeability and H2 S could be detected within the cells. In situ visualization of H2 S was performed on the hippocampal slices of normal mice with probe EPS-HS. The probe will be applied for better treatment of neurological deficits caused by damage to the hippocampus.